Intracranial and Spinal MR Imaging Findings Associated with Krabbe’s Disease: Case Report - Given II, Curtis A.; Santos, Cesar C.; Durden, David D. (American Journal of Neuroradiology, 2001)
Summary: Krabbe’s disease is an autosomal recessive leukodystrophy with well-documented intracranial findings on both CT scans and MR images. We herein present what is thought to be the second case of Krabbe’s disease with spinal involvement shown on MR images as abnormal contrast enhancement of the lumbosacral nerve roots. The typical intracranial findings of T2 hyperintensity without contrast enhancement were present within the periventricular white matter, but there was no area of abnormal signal intensity or enhancement within the substance of the spinal cord. We briefly review the pathophysiology, clinical presentation, and imaging findings of Krabbe’s disease. Spinal abnormalities may precede the onset of brain abnormalities, and MR imaging may be a useful diagnostic tool in cases of Krabbe’s disease and other leukodystrophies.